The RIG-I Signal Pathway Mediated Panax notoginseng Saponin Anti-Inflammatory Effect in Ischemia Stroke. (21st August 2021) - Zhang, Chujun; Zhang, Sai; Wang, Lanxiang; Kang, Soyeon; Ma, Jiabao; Liu, Shihao; Hu, Yanhong; Zhang, Fan; Sun, Tianshi; Dong, Yixin; Li, Tenghui; Li, Weihong; et al.
Abstract : Panax notoginseng saponins (PNS), the main bioactive constituents of a traditional Chinese herb Panax notoginseng, were commonly used for ischemic stroke in China. However, the associated cellular and molecular mechanisms of PNS have not been well examined. This study aimed to decipher the underlying molecular target of PNS in the treatment of cerebral ischemia. The oxygen-glucose-deprived (OGD) model of rat brain microvascular endothelial cells (BMECs) was used in this study. The alteration of gene expression in rat BMECs after PNS treatment was measured by microarray and indicated that there were 38 signaling pathways regulated by PNS. Among them, RIG-I receptor and related signaling molecules TNF receptor-associated factor 2 (Traf2) and nuclear factor-kappa B (NF- κ B) were significantly suppressed by PNS, which was verified again in OGD-induced BMECs measured by FQ-PCR and western blotting and in middle cerebral artery occlusion (MCAO) rats measured by immunohistochemistry. The levels of TNF- α, IL-8, and the downstream cytokines regulated by RIG-I receptor pathway were also decreased by PNS. Meanwhile, the neurological evaluation, hematoxylin and eosin (HE) staining, and Evans blue staining were conducted to evaluate the effect of PNS in MCAO rats. Results showed PNS significantly improved functional outcome and cerebral vascular leakage. Flow cytometry showed the number of the inflammatory cells infiltrated in brain tissue was decreased in PNS treatment. Our results identified that RIG-I signaling pathway mediated anti-inflammatory properties of PNS in cerebral ischemia, which provided the novel insights of PNS application in clinics.